PERAN KEUCHIK DALAM PEMBANGUNAN KAMPUNG TELUK AMBUN KECAMATAN SINGKIL KABUPATEN ACEH SINGKIL - Rahmat Syafrizaldi; Fedry Saputra; Roni Hidayat (CONSTITUO : Jurnal Riset Hukum Kenegaraan dan Politik, 2024)
The Keuchik/Village Head is the one who sets the wheels in motion to organize village government, carry out village development, foster village community, and empower village community. The Keuchik has the authority to lead the implementation of village government and carry out other authorities in accordance with statutory regulations. In this research, an in-depth analysis was carried out on the role of Keuchik in the development of Teluk Ambun Village, Singkil District, Aceh Singkil Regency. The research uses qualitative research methods with a descriptive approach. In this research, it is described and analyzed in more depth regarding the topics raised. The Keuchik's Role in the Development of Teluk Ambun Village, Singkil District, Aceh Regency. Singkil has carried out his duties and roles well as expected, both as a motivator, mobilizer and facilitator. The role of the keuchik is very important in determining the progress of the development of Teluk Ambun Village. The obstacles found in the community's participation in the village are still less active. The low level of education in Teluk Ambun Village is one of the reasons for the lack of involvement of the village community in development, the village community believes that the task of village development is only delegated to the Keuchik and the apparatus as a whole without any community intervention. Apart from educational factors, work is also an obstacle that the keuchik finds in development in Teluk Ambun Village.